RETRACTED: Optimization of conditions for cultivation of pathogens of infectious rhinotracheitis and viral diarrhea - Karimullina Ilsiyar; Yarullin Ainur; Mukhammadiev Rishat; Mukhammadiev Rinat; Mingaleev Danil; Khusainova Gulnara; Sorokina Diana; Gumerov Vali (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001